2021
DOI: 10.3390/ijms22168675
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Derived Organoids of Cholangiocarcinoma

Abstract: Cholangiocarcinoma (CC) is an aggressive malignancy with an inferior prognosis due to limited systemic treatment options. As preclinical models such as CC cell lines are extremely rare, this manuscript reports a protocol of cholangiocarcinoma patient-derived organoid culture as well as a protocol for the transition of 3D organoid lines to 2D cell lines. Tissue samples of non-cancer bile duct and cholangiocarcinoma were obtained during surgical resection. Organoid lines were generated following a standardized p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 66 publications
0
21
0
Order By: Relevance
“…There are some reports of screening only FDA-approved drugs or clinically available agents for treatment because it is impractical to screen compounds that cannot be used clinically [ 58 , 74 , 75 , 76 , 77 ]. Ramamoorthy et al developed a multicellular lung organoid called primitive lung-in-a-dish (PLiD), which mimics the lung microstructure with air sac-like alveoli and produces lung surfactant protein.…”
Section: Personalized Medicinementioning
confidence: 99%
“…There are some reports of screening only FDA-approved drugs or clinically available agents for treatment because it is impractical to screen compounds that cannot be used clinically [ 58 , 74 , 75 , 76 , 77 ]. Ramamoorthy et al developed a multicellular lung organoid called primitive lung-in-a-dish (PLiD), which mimics the lung microstructure with air sac-like alveoli and produces lung surfactant protein.…”
Section: Personalized Medicinementioning
confidence: 99%
“…In 2011, Sato et al first established an organoid culture system of benign and malign PDOs of the colon and esophagus [ 30 ]. These PDOs resemble the individual histopathological features, tumor stage, genetic landscape as well as cellular heterogeneity of the original tumor of the individual patient [ 54 , 55 , 56 , 57 , 58 , 59 ]. This applies not only for primary tumors but has also been shown for organoids derived from metastases or even from extremely rare circulating tumor cells (CTCs) [ 60 , 61 , 62 ].…”
Section: Organoids As An Enhanced Model For (Personalized) Drug Screeningmentioning
confidence: 99%
“…Recently developed organoid culture techniques enable formation of adult stem cell-derived cancer organoids from cholangiocarcinoma specimens. [12][13][14][15][16][17] Importantly, the resulting organoids show similar phenotypic and genetic characteristics compared with the original primary tumor. A previous study showed that even small biopsy samples are su cient for the generation of tissue-derived organoids.…”
Section: Introductionmentioning
confidence: 97%